Electron transport chain activity is a predictor and target for venetoclax sensitivity in multiple myeloma - Richa Bajpai (Nature Portfolio, 2020)
Venetoclax monotherapy is effective in 40% of t(11:14) positive multiple myeloma (MM). Here, the authors show that electron transport chain complex I (CI) and complex II (CII) activity predict MM sensitivity to venetoclax, and inhibition of CI with IACS-010759 or CII with TTFA increase sensitivity.